PENGARUH INFLASI DAN SUKU BUNGA TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Adinda Tri DZ; Seli Marsela; Rena Oktaviani; Naysha Rahmadhani; Rasya Islammartasya; Jolianis (STKIP Subang, 2026)
Indonesia's macroeconomic stability over the past few decades has been characterized by dynamics influenced by fluctuations in inflation and interest rate changes, two key indicators that are the primary focus of monetary policy. However, previous studies have shown inconsistent results regarding how these two variables affect economic growth, necessitating updated analyses with longer data sets. This study aims to analyze the influence of inflation and interest rates on Indonesia's economic growth based on time series data from 1990 to 2024. This study is associative, using secondary data obtained from Statistics Indonesia and the World Bank. The analysis was conducted using stationarity tests and multiple linear regression. The results indicate that inflation has a significant and negative effect on economic growth, while interest rates have no significant effect. This finding indicates that inflation stabilization plays a more dominant role in supporting economic growth than interest rate management during the study period. This study provides an empirical contribution to the Indonesian macroeconomic literature by emphasizing the importance of long-term inflation control policies to maintain sustainable national economic growth.